A Review on Teachers and Students Engagement in Mathematics Learning: A Critical Reflection on Nepalese Context - Thapa, Dal Bahadur (Dhaulagiri Journal of Contemporary Issues, 2023)
This article focuses on the engagement of students and teachers in mathematics learning within Nepalese classroom. Mathematical interaction is considered a significant concern in Nepal, particularly due to the multicultural and multilingual nature of the classrooms. Nepalese students come from diverse cultural and linguistic background, posing challenges in implementing constructive approaches to teaching mathematics. The teacher-student interaction is regarded from a cognitive perspective, recognizing both parties as mutually authoritative subjects actively interpreting and anticipating within the classroom. The primary objective of this article is to investigate the dynamics and effective use of constructivist principles in mathematics classrooms in Nepal. Through qualitative research methods, the study has the potential to offer valuable insights into the challenges and interactions between teachers and students, especially in multicultural and multilingual settings. By exploring these dynamics and analyzing the successful application of constructivist principles, this research can have a positive impact on mathematics education and instructional strategies in Nepalese classrooms, ultimately leading to improved student engagement and learning outcomes.